Solomons' organic chemistry - Solomons, T. W. Graham; Fryhle, Craig B.; Snyder, S. A. (John Wiley & Sons, 2016)
Readers will find that this highly acclaimed book offers a balanced approach to functional groups and mechanisms. The presentation of key concepts will help them master basic skills. Throughout the focus is placed on the ideas of organic chemistry and backs them up with illustrations and challenging problems.